Financialization in the Automotive Industry: Shareholders, Managers, and Salaries. Issue 3 (3rd July 2019) - do Carmo, Marcelo; Neto, Mario Sacomano; Donadone, Julio Cesar
Abstract: Automakers are facing a growing process of financialization that can be characterized by the preference to value capital through financial activities as more profitable than by productive activities. The aim of this article is to study the financialization of the automotive industry by analyzing the five largest automakers in the world: Toyota, Volkswagen, Hyundai, General Motors (GM) and Ford. The profitability of financial activities was compared to that of productive activities; shareholder structure; share acquisitions; origin of top managers; compensation to executives; employee salaries; dividend payments to shareholders and employment. The results showed that increasingly more financial activities are fundamental to businesses dominated by major shareholders. Dividend payments have shown compliance to shareholder value maximization principles. Compensation to executives has shown that there is a layer of highly paid top managers, while in the workforce, salaries are below the average of the countries in which the automakers operate. The proportion of times that a CEO's earnings outweigh the average earnings of less skilled workers is hundreds of times. Employment has been changing, with significant increases in China, for instance. This article aims to improve the knowledge of this important sector of world industry and contribute to development of economic sociology.